Remuneração Docente de Educação Básica em Tempos de Austeridade - Maria do Socorro Sales Felipe Bezerra (2023)
The present study analyzes the impact of austerity measures that took place in the Brazilian political-economic system from 2010 to 2020, which affected the remuneration policy of teachers in the public school systems of Brazilian state capitals. The period in focus was marked by significant changes in educational policy with a view to reproducing the teaching workforce, in terms of reducing public spending on education and reducing the expectations set forth in Law Nº. 11,738/2008, which established the Professional Salary Floor (PSPN). The challenges of teacher remuneration and the education financing policy scenario are highlighted, which is linked to the Basic Education Maintenance and Development Fund and the Professional Development of Education Professionals Fund (Fundeb), which, in turn, guarantees the Career and Salary Plan (PCCR) to teachers in each federative unit. In this scenario, in the economic and conjunctural field, among the main decisions was the promulgation of Constitutional Amendment Nº. 95, of December 16, 2016, which established the New Fiscal Regime (NRF), which reduced public spending on social policies. This research hypothesis is that the scenario between 2010 and 2020 configured the process of disarticulation of the remuneration policy, with greater success starting in 2015, a period in which political and economic forces in the country began to act together with the purpose of redesigning the teaching workforce in view of the fiscal austerity context. The study worked with the PCCR of each capital, educational legislation, Budget Execution Reports (REO), data from the Annual Social Information Report (RAIS), and data from the Public Education Budget Information System (SIOPE), aiming to verify the actions of the Central State in intersection with the local sphere regarding the valorization of teacher work through remuneration in the period from 2010 to 2020. The study considered that teacher remuneration was not realized as required by law and also suffered interferences from the economic capacity of the State, especially from 2015 onwards. In the last five year-period, the devaluation of teachers seems to have a close relationship with the economic crisis and with the trend towards conjunctural change in the neoliberal model, based on a rigid reference to preserving public accounts, at the expense of the teacher appreciation.Keywords: Educational policy. Teacher remuneration. Municipal education networks. Brazilian capitals. Fiscal austerity